T.U.N.E. Band : a smart wearable device promoting emotion recognition in individuals with autism spectrum disorder. - Amagsila, Jeric C. Bitara, Jan Vicent S. De Guzman, April Yzabelle M. Ferrer, Marck Gelbert C. Molo, Jericho B. 4 0 16; 5
u
Undergraduate Thesis : (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2